PERAN TOKSIKOLOGI FORENSIK DALAM MENGUNGKAP KASUS KERACUNAN DAN PENCEMARAN LINGKUNGAN - Budiawan, Dr. rer. nat. (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2008)
In Indonesia, there are many cases of poisoning and environmental pollution which are hardto reveal, mostly because there are insufficient data needed to proof the cause of the case, i.e., BuyatCase, poisoning case of residents in Magelang, the death of Munir (Human Right Activist), andfood poisoning which often occurs in Indonesia. The lack of knowledge and understanding of therequirements to make a conclusion about cases dealing with poisoning and environmental pollutionmakes the strategy for collecting data collection is often incorrect. Through forensic toxicology, themechanism and fate of toxic substances in living organisms and its environmental fate could beunderstood, and make investigation easy, and the main cause of poisoning or polution could beconcluded. Biomonitoring is one of the sciences supporting investigation of scientifical proof inForensic Toxicology. Through the determination of biomarker, we could describe the exposure oftoxic substances to a person, population or species in the environment, and also could describe thetoxic substance which cause poisoning or pollution. The main concern in forensic toxicology is notthe legal aspect output from toxicological investigation, but it is the technology and tehnicques inobtaining and intepreting results. Through the understanding of toxicology and the support ofrelated sciences, the important and right strategy or measures could be taken to make the rightconclusion in dealing with poisoning and environmental pollution cases.
Keywords: Toxicology, toxic substances, biomonitoring, biomarker